Non-alcoholic fatty liver disease induces signs of Alzheimer's disease (AD) in wild-type mice and accelerates pathological signs of AD in an AD model. Issue 1 (December 2016) - Kim, Do-Geun; Krenz, Antje; Toussaint, Leon; Maurer, Kirk; Robinson, Sudie-Ann; Yan, Angela; Torres, Luisa; Bynoe, Margaret
Abstract Background Non-alcoholic fatty liver disease (NAFLD) is a chronic liver disease afflicting about one third of the world's population and 30 % of the US population. It is induced by consumption of high-lipid diets and is characterized by liver inflammation and subsequent liver pathology. Obesity and consumption of a high-fat diet are known to increase the risk of Alzheimer's disease (AD). Here, we investigated NAFLD-induced liver inflammation in the pathogenesis of AD. Methods WT and APP-Tg mice were fed with a standard diet (SD) or a high-fat diet (HFD) for 2, 5 months, or 1 year to induce NAFLD. Another set of APP-Tg mice were removed from HFD after 2 months and put back on SD for 3 months. Results During acute phase NAFLD, WT and APP-Tg mice developed significant liver inflammation and pathology that coincided with increased numbers of activated microglial cells in the brain, increased inflammatory cytokine profile, and increased expression of toll-like receptors. Chronic NAFLD induced advanced pathological signs of AD in both WT and APP-Tg mice, and also induced neuronal apoptosis. We observed decreased brain expression of low-density lipoprotein receptor-related protein-1 (LRP-1) which is involved in β-amyloid clearance, in both WT and APP-Tg mice after ongoing administration of the HFD. LRP-1 expression correlated with advanced signs of AD over the course of chronic NAFLD. Removal of mice from HFD during acute NAFLD reversed liver pathology, decreased signs of activated microglial cells and neuro-inflammation, and decreased β-amyloid plaque load. Conclusions Our findings indicate that chronic inflammation induced outside the brain is sufficient to induce neurodegeneration in the absence of genetic predisposition.